Coronary artery rotation in native and stented porcine coronary arteries. Issue 6 (24th August 2017) - Challa, Karthik K.; Kansal, Mayank M.; Frazin, Leon; Nikanorov, Alex; Kohler, Robert; Martinsen, Brad J.; Vidovich, Mladen I.
Abstract: Introduction: Coronary arteries are exposed to several complex biomechanical forces during the cardiac cycle. These biomechanical forces potentially contribute to both native coronary artery disease, development of atherosclerosis and eventual stent failure. The aim of the present study was to characterize and define coronary artery axial rotation and the effect of stent implantation on this biomechanical factor. Methods: Intravascular ultrasound (IVUS) images were obtained from porcine coronary arteries and analyzed in ultrasound analysis software used to evaluate myocardial strain and torsion in echocardiography. In this study the software was utilized for a novel application to evaluate coronary artery rotation and time‐to‐peak (TTP) rotation in porcine coronary arteries. Clockwise (CW) and counterclockwise (CCW) rotation of coronary arteries during the cardiac cycle and (TTP) rotation were measured. Results: A total of 11 (4 LAD, 4 LCX, 3 RCA) coronary artery segments were independently analyzed pre‐ and post‐stent implantation for a total of 22 IVUS runs. CW and CCW rotation and TTP varied widely within coronary artery segments and between different coronary arteries. Stent implantation impacted degree, direction and TTP of coronary rotation. Measurement reliability was assessed and the intraclass correlation coefficient for maximum average CCW was 0.990 (95% confidence interval 0.980–0.996, P < 0.0001), indicating excellent agreement. Conclusions: Coronary arteries display wide spectrum of CW and CCW rotation during the cardiac cycle. Coronary stents impact the degree and direction of coronary artery rotation. The implications of these findings on development of atherosclerosis and stent failure require further investigation.